(3TQM GdOQI GdaGNQIs - (3EHQGgje Hf MjOQ Hf CMeO Hf MjOQ GdcQOi GdMSfj GHGOis; (3fhQ GdOjf YHO GdQMef Hf CMeO Hf eMeO GdLGej GdfbTHfOj, GdLGej,J (B898 (3g` s ((3eMeO YHO GddWja GdMfHdj s)
(3ChdgG (B:s
(3MeOkG dc jG ef GQJSe LeGdg ai eQGjG eXGgQ GdehLhOGJ hHYO jbhd GdYHO deG QCjJ gPg GdOQI eTJedI Ydi eNOQGJ dGFMI ef YGde GddGghJ aCQOJ Cf CTQMgG s
(3BNQgG (B:s
(3hPdc dCf PGJg bO cKQJ Ydjg GdGYJHGQGJ ai eQJHI GdYde adG jchf Mjf gPG GdGfHSGW GdYjfi hGMO ef LejY GdLgGJ Je s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdSGOSs
(3hQO GdYfhGf GdCUdi ai cX (B742/1s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B67s
Keywords: (3GdJUha hGdBOGH GdTQYjIs